A method for photocatalytic conversion of methanol to formaldehyde and hydrogen
Patent Information
- Application Number
- CN202610535701.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-22
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2046-04-22
AI Technical Summary
甲醇重整制氢虽被认为是分布式制氢的重要方向,但传统热催化甲醇重整制氢技术需在200℃~300℃的高温条件下进行,反应路径不可控,甲醇易发生完全重整与深度脱氢副反应,生产过程中仍会生成大量二氧化碳与一氧化碳气体,且生成的一氧化碳还会严重毒化催化剂,必须配套复杂的气体净化与后处理单元,存在工艺路线复杂、设备投入大、生产运行成本高的问题
[0006]According to embodiments of this application, a method for photocatalytic conversion of methanol to formaldehyde and hydrogen uses anatase phase titanium dioxide {001} nanocrystals loaded with platinum nanoparticles with an average size of 2nm~6nm as a photocatalyst, and a methanol-water aqueous solution with a methanol-to-water volume ratio of (90~60):(10~40) as the reaction substrate. Under mild conditions of ultraviolet light irradiation and sealed oxygen-free environment, the method utilizes the platinum-titanium dioxide interface sites and titanium dioxide support sites for synergistic catalysis, and combines the regulatory effect of water to optimize the methanol conversion pathway, to carry out the photocatalytic dehydrogenation of methanol to formaldehyde and hydrogen. This promotes the directional and selective dehydrogenation of methoxy intermediates, effectively suppresses the excessive conversion of formaldehyde by side reactions, and enables the synergistic co-production of formaldehyde and hydrogen under oxygen-free room temperature conditions. The formaldehyde selectivity can reach more than 91%, and the methanol conversion rate can reach more than 0.6%, exhibiting both good catalytic stability and promising prospects for industrial application.
Smart Images

Figure CN122059816B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of formaldehyde and hydrogen preparation technology, and particularly relates to a method for photocatalytic conversion of methanol to prepare formaldehyde and hydrogen. Background Technology
[0002] With the acceleration of global industrialization and the continuous rise in energy demand, the carbon emissions and environmental pollution caused by the large-scale consumption of traditional fossil fuels are becoming increasingly serious. Hydrogen, as an ideal clean energy carrier with high energy density and zero-pollution combustion products, has become a major component of the future environmentally friendly energy system. Currently, mainstream industrial hydrogen production technologies still rely primarily on natural gas steam reforming and coal gasification routes. These routes not only depend on non-renewable fossil fuels but also emit large amounts of carbon dioxide during the production process. While methanol reforming for hydrogen production is considered an important direction for distributed hydrogen production, traditional thermocatalytic methanol reforming technology requires high-temperature conditions of 200℃~300℃, making the reaction path uncontrollable. Methanol is prone to complete reforming and deep dehydrogenation side reactions, still generating large amounts of carbon dioxide and carbon monoxide during production. Furthermore, the generated carbon monoxide can severely poison the catalyst, necessitating complex gas purification and post-treatment units. This results in complex process routes, large equipment investment, and high production and operating costs. Summary of the Invention
[0003] In view of this, the main objective of this application is to provide a method for the photocatalytic conversion of methanol to formaldehyde and hydrogen, in order to at least partially solve at least one of the aforementioned technical problems.
[0004] To achieve the above objectives, the technical solution of this application is as follows.
[0005] In one aspect of this application, a method for photocatalytic conversion of methanol to formaldehyde and hydrogen is provided, comprising: mixing an aqueous methanol solution and a photocatalyst under closed, oxygen-free conditions and placing the mixture under an ultraviolet light source to carry out a photocatalytic dehydrogenation reaction of methanol to produce formaldehyde and hydrogen, thereby preparing formaldehyde and hydrogen; wherein the photocatalyst is anatase phase titanium dioxide {001} nanocrystals with platinum nanoparticles loaded on the surface, the average size of the platinum nanoparticles being 2 nm to 6 nm; and the volume ratio of methanol to water in the aqueous methanol solution being (90 to 60): (10 to 40).
[0006] According to embodiments of this application, a method for photocatalytic conversion of methanol to formaldehyde and hydrogen uses anatase phase titanium dioxide {001} nanocrystals loaded with platinum nanoparticles with an average size of 2nm~6nm as a photocatalyst, and a methanol-water aqueous solution with a methanol-to-water volume ratio of (90~60):(10~40) as the reaction substrate. Under mild conditions of ultraviolet light irradiation and sealed oxygen-free environment, the method utilizes the platinum-titanium dioxide interface sites and titanium dioxide support sites for synergistic catalysis, and combines the regulatory effect of water to optimize the methanol conversion pathway, to carry out the photocatalytic dehydrogenation of methanol to formaldehyde and hydrogen. This promotes the directional and selective dehydrogenation of methoxy intermediates, effectively suppresses the excessive conversion of formaldehyde by side reactions, and enables the synergistic co-production of formaldehyde and hydrogen under oxygen-free room temperature conditions. The formaldehyde selectivity can reach more than 91%, and the methanol conversion rate can reach more than 0.6%, exhibiting both good catalytic stability and promising prospects for industrial application. Attached Figure Description
[0007] Figure 1 These are high-resolution transmission electron microscope (TEM) images of the photocatalysts in Examples 1 to 3 of this application, wherein a is a TEM image of photocatalyst 1 in Example 1; b is a TEM image of photocatalyst 2 in Example 2; and c is a TEM image of photocatalyst 3 in Example 3.
[0008] Figure 2 This is a comparison graph showing the hydrogen generation rate, formaldehyde generation rate, and hydrogen to formaldehyde yield ratio in the photocatalytic reactions of Comparative Examples 1, 3, and 4 of this application.
[0009] Figure 3 This is a comparison graph showing the hydrogen generation rate, formaldehyde generation rate, and hydrogen to formaldehyde yield ratio in the photocatalytic reactions of Examples 1 to 3 of this application.
[0010] Figure 4 This is a comparison graph showing the hydrogen generation rate, formaldehyde generation rate, and hydrogen to formaldehyde yield ratio in the photocatalytic reactions of Examples 1, 4-6, and Comparative Examples 1-2 of this application. Detailed Implementation
[0011] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with specific embodiments.
[0012] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this application.
[0013] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of this application. The terms “comprising,” “including,” etc., as used herein indicate the presence of the stated features, steps, operations, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, or components.
[0014] In the process of realizing this application, it was discovered that photocatalytic methanol-to-hydrogen production can realize the conversion of solar energy to chemical energy under mild conditions. However, in the existing photocatalytic system, although the photocatalyst can improve the activation ability of methanol, it is easy to cause deep dehydrogenation and excessive oxidation side reactions of the generated formaldehyde, resulting in low selectivity of the target product. At the same time, it is easy to cause the accumulation of formate on the surface of the photocatalyst, making it impossible to achieve efficient synergistic preparation of hydrogen and formaldehyde.
[0015] Although titanium dioxide photocatalysts loaded with platinum nanoparticles can be used for photocatalytic methanol conversion to formaldehyde and hydrogen, the platinum sites have a strong ability to deeply convert oxygen-containing intermediates. The generated formaldehyde is prone to further deep dehydrogenation and over-oxidation reactions, which leads to the accumulation of formate on the surface of the photocatalyst and the generation of carbon monoxide (CO) and carbon dioxide (CO2) gases. This not only results in a significant reduction in the selectivity and yield of formaldehyde, but CO also poisons the active sites, making it difficult to achieve efficient synergistic preparation of hydrogen and formaldehyde.
[0016] Based on this, this application provides a method for photocatalytic conversion of methanol to formaldehyde and hydrogen. Through an acid-base regulation strategy without organic stabilizers, platinum nanoparticles with an average size of 2nm~6nm supported on anatase phase titanium dioxide {001} nanocrystals are used as the photocatalyst. A methanol-water aqueous solution with a volume ratio of (90~60):(10~40) is used as the reaction substrate. Under mild conditions of ultraviolet light irradiation and room temperature without oxygen, the method utilizes the synergistic catalysis of the platinum-titanium dioxide interface sites and the titanium dioxide support sites, coupled with the synergistic effect of water, to regulate the methanol conversion pathway, promote the directional and selective dehydrogenation of the methoxy intermediate, effectively suppress the excessive conversion of formaldehyde by side reactions, and ultimately achieve the synergistic co-production of formaldehyde and hydrogen.
[0017] According to an embodiment of one aspect of this application, a method for photocatalytic conversion of methanol to formaldehyde and hydrogen is proposed, comprising: mixing an aqueous methanol solution and a photocatalyst under closed anaerobic conditions and placing the mixture under an ultraviolet light source to carry out a photocatalytic dehydrogenation reaction of methanol to produce formaldehyde and hydrogen, thereby preparing formaldehyde and hydrogen, wherein the photocatalyst is anatase phase titanium dioxide {001} nanocrystals with platinum nanoparticles loaded on the surface, the average size of the platinum nanoparticles being 2nm~6nm; the volume ratio of methanol to water in the aqueous methanol solution is (90~60):(10~40).
[0018] According to some specific embodiments of this application, the average size of the platinum nanoparticles can be, for example, 2nm, 3nm, 4nm, 5nm, 6nm, etc., and the volume ratio of methanol to water can be, for example, 90:10, 80:20, 70:30, 60:40, etc.
[0019] According to some specific embodiments of this application, the oxygen-free condition can be an inert gas nitrogen (N2) environment.
[0020] According to embodiments of this application, in a closed, oxygen-free photocatalytic reaction system, the conversion of methanol-water solution on the surface of the photocatalyst involves a competing process between primary and secondary reactions: methanol molecules first adsorb onto the surface of the photocatalyst and then dissociate to form methoxy groups (…). The intermediate, methoxy intermediate, is selectively dehydrogenated to formaldehyde (HCHO), and hydrogen (H2) is produced simultaneously. However, the generated formaldehyde is prone to non-target side reactions, namely: further deep dehydrogenation to form carbon monoxide (CO), or excessive oxidation to form formate strongly adsorbed on the surface of the photocatalyst. This not only leads to a decrease in formaldehyde selectivity, but also causes the active sites on the surface of the photocatalyst to be poisoned by CO, making it difficult to achieve efficient synergistic preparation of formaldehyde and hydrogen.
[0021] This application uses anatase-phase titanium dioxide (TiO2){001} nanocrystals with platinum (Pt) nanoparticles supported on their surface as a photocatalyst. The anatase-phase titanium dioxide {001} nanocrystals exhibit highly active five-coordinated titanium (TiO2) on their surface. 5C The site is the main adsorption and activation site for the methoxy intermediate. However, the substance that is truly easily oxidized by photogenerated holes in the photocatalytic system is not molecular methanol, but rather Ti. 5C The adsorption of methoxy intermediates at the sites, and the formation and directional transformation of methoxy intermediates, are the main factors determining reaction efficiency and product selectivity. Pt nanoparticles supported on the photocatalyst surface form a platinum-titanium dioxide (Pt-TiO2) Schottky junction, creating a well-defined bifunctional synergistic active interface.
[0022] In this Pt-TiO2 Schottky junction, the TiO2 side more readily adsorbs alcohol oxygen species (such as methoxy intermediates), receives and transfers photogenerated holes, and activates the carbon-hydrogen (CH) and oxygen-hydrogen (OH) bonds of methanol molecules. The Pt side more readily receives photogenerated electrons from the TiO2 conduction band, gathers surface-adsorbed hydrogen species, and promotes hydrogen generation. Simultaneously, it lowers the desorption barrier for molecular hydrogen, allowing surface hydrogen species to rapidly desorb as hydrogen gas at lower temperatures. This bifunctional synergistic active interface structure controls the oxidation half-reaction at the formaldehyde generation stage and the reduction half-reaction along the hydrogen generation pathway, preventing formaldehyde from transforming to deeper oxidation states and ensuring selectivity in the reaction pathway.
[0023] Meanwhile, the loading of Pt nanoparticles can effectively promote the dissociation of methanol at the Pt-TiO2 interface to generate methoxy intermediates, and promote the separation of photogenerated electron-hole pairs by enhancing the interfacial band bending, thereby accelerating the photo-oxidation process of methanol. The continuous reaction of methanol molecules requires them to be firmly anchored as methoxy intermediates first. The binding stability of the generated formaldehyde with the Pt-TiO2 interface is much lower than that of the methoxy intermediates, which allows formaldehyde to be quickly desorbed into the liquid or gas phase after generation. This significantly shortens its residence time on the photocatalyst surface and reduces the probability of it being further oxidized by photogenerated holes, surface hydroxyl groups, or reactive oxygen species, thereby further improving the selectivity of formaldehyde.
[0024] This application regulates the average size of Pt nanoparticles in the photocatalyst to 2nm~6nm, further amplifying the catalytic advantages of the bifunctional synergistic interface. This allows the photocatalyst to co-catalyze the production of formaldehyde and hydrogen from methanol solution in the photocatalytic dehydrogenation reaction by utilizing the platinum-titanium dioxide (Pt-TiO2) interface sites and the anatase titanium dioxide (TiO2) support sites.
[0025] The small-sized (average size 2nm~6nm) Pt nanoparticles result in a higher proportion of Pt-TiO2 interface sites and a larger interfacial perimeter in the photocatalyst. This not only promotes the conversion of methanol to formaldehyde at the Pt-TiO2 interface site region but also enhances the conversion ability of methanol to formaldehyde at adjacent TiO2 support sites. This allows both the Pt-TiO2 interface sites and the TiO2 support sites to participate in the formaldehyde generation process, ultimately exhibiting higher formaldehyde and hydrogen generation activity. This is because small-sized Pt nanoparticles, especially those with an average size of 2nm~6nm, have higher surface energy and lower coordination number, resulting in a higher work function and stronger electron affinity. They can more efficiently extract photogenerated electrons from the TiO2 conduction band, forming a stronger Schottky barrier and band bending at the interface. This leads to a more concentrated distribution of photogenerated holes near the interface, significantly increasing the effective hole concentration on the TiO2 surface, and thus more efficiently oxidizing TiO2. 5C The formation of formaldehyde from the methoxy intermediate at the site makes methanol conversion more likely to proceed along the main reaction pathway of selective dehydrogenation to formaldehyde, fundamentally inhibiting the side reactions of deep formaldehyde conversion.
[0026] Meanwhile, this application achieves a synergistic coupling effect between small-sized platinum (Pt) nanoparticles and water by adjusting the volume ratio of methanol to water in the methanol-water solution to (90~60):(10~40), further enhancing the photocatalytic hydrogen production performance on the original basis, while also further strengthening the selectivity of formaldehyde. This synergistic coupling effect is mainly achieved through the following four aspects.
[0027] First, water can dissociate on the surface of the photocatalyst to generate hydroxyl groups and protons. The hydroxyl groups generated can promote the rapid dissociation of methanol to form the key reaction intermediate methoxy group, thereby increasing the in-situ generation of the methoxy intermediate. Under light irradiation, water can also react with photogenerated electrons to generate hydroxyl groups and hydroxyl radicals (·OH). This can reduce the accumulation of photogenerated electrons on the surface of the photocatalyst, inhibit the recombination of photogenerated electron-hole pairs, and release more photogenerated holes to participate in the oxidation reaction of methanol. The generated hydroxyl radicals can also directly oxidize the methoxy intermediate to formaldehyde, thereby simultaneously improving the reaction activity and the selectivity of the target product formaldehyde.
[0028] Second, water can participate in the conversion of CO generated during the reaction, enabling the CO formed by deep dehydrogenation of formaldehyde and retained on the surface of the photocatalyst to be further converted into carbon dioxide (CO2), which is more easily desorbed, effectively reducing the occupation and poisoning effect of CO on the active sites. Furthermore, the small-sized Pt nanoparticles loaded on the photocatalyst of this application have a stronger methanol activation ability and generate more CO through deep dehydrogenation. The introduction of water can more significantly release the active sites, ensuring the continuous and efficient progress of the photocatalytic reaction.
[0029] Third, the presence of water can promote the protonation of formate intermediates that are stably adsorbed on the surface of the photocatalyst, forming formic acid species that are more easily transformed. Formic acid can be further decomposed to generate hydrogen, providing an additional hydrogen production channel for the reaction and further improving the hydrogen production efficiency of the system.
[0030] Fourth, water can also stabilize the formaldehyde produced in the reaction as hydrated formaldehyde, i.e., methanediol, in the system, reducing the tendency of formaldehyde to continue to undergo deep dehydrogenation to produce CO. Furthermore, the small-sized Pt nanoparticles loaded on the photocatalyst of this application have a stronger desorption promoting effect on formaldehyde. Under the synergistic effect of the two, formaldehyde and its hydrated form can leave the catalytic active center more quickly, avoiding it from staying on the surface of the photocatalyst for too long and undergoing deep transformation. At the same time, it can continuously expose more Pt-TiO2 interface sites and adjacent TiO2 support sites for the adsorption and activation of new methanol molecules, forming a benign catalytic cycle, and finally achieving efficient co-production of formaldehyde and hydrogen.
[0031] According to an embodiment of this application, the volume ratio of methanol to water in the methanol-water solution is 70:30.
[0032] According to embodiments of this application, when the volume ratio of methanol to water in the methanol-water solution is 70:30, the reaction system exhibits superior photocatalytic activity. At this volume ratio, the effective adsorption coverage of methanol on the photocatalyst surface and the efficiency of scavenging photogenerated holes can achieve a better matching state with the interfacial hydrogen bond network and proton transfer environment constructed with water. This fully leverages the synergistic coupling effect between the small-sized (2~6nm) Pt nanoparticles in the photocatalyst and water, simultaneously promoting methanol dissociation and the directional conversion of methoxy intermediates, maximizing the catalytic turnover efficiency per unit active site.
[0033] When the methanol content is too low (methanol to water volume ratio below 70:30, especially below 60:40), the methanol effectively covers the photocatalyst interface, resulting in a decrease in the efficiency of photogenerated hole removal and an increase in photogenerated carrier recombination. This makes it difficult to provide sufficient methoxy intermediates for the photocatalytic reaction, leading to a decrease in reaction activity and product formation rate. When the methanol content is too high (methanol to water volume ratio above 70:30, especially above 90:10), the interfacial synergy between water and platinum active sites is weakened, making it difficult to effectively exert the positive effects of water in promoting methanol dissociation, removing CO poisoning sites, and stabilizing formaldehyde desorption. At the same time, excessive methanol tends to form an excessively thick adsorption layer on the photocatalyst surface, creating an unfavorable local solvation environment that hinders the effective contact between methanol molecules and active sites, thereby reducing the catalytic turnover efficiency per unit active site and ultimately leading to a decrease in reaction activity.
[0034] According to embodiments of this application, the average size of the platinum nanoparticles is 2 nm. This size is within the adjustable range of 2 nm to 6 nm for the average size of the platinum nanoparticles, balancing catalytic activity, product selectivity, structural stability, and atom utilization. Platinum nanoparticles with an average size of 2 nm have a higher interfacial perimeter-to-volume ratio, allowing the photocatalyst to provide more platinum-titanium dioxide interfacial active sites per unit loading, resulting in higher platinum atom utilization. Platinum nanoparticles of this size have a high proportion of low-coordination atoms and a better work function matching with the titanium dioxide band structure, effectively promoting photogenerated carrier separation and increasing the effective hole concentration on the surface of anatase phase titanium dioxide {001} nanocrystals. Simultaneously, the surface site structure of the 2 nm average size platinum nanoparticles can match the requirements for directional methanol dehydrogenation, efficiently activating the CH bonds of methanol without over-activating formaldehyde and triggering deep dehydrogenation side reactions, achieving a good balance between catalytic activity and selectivity.
[0035] According to the embodiments of this application, the amount of photocatalyst added to the methanol solution is 0.1 g / L to 0.3 g / L, for example, 0.1 g / L, 0.15 g / L, 0.2 g / L, 0.25 g / L, 0.3 g / L, etc. The photocatalyst addition range of 0.1 g / L to 0.3 g / L can effectively balance the supply of active sites and the utilization efficiency of ultraviolet light in the reaction system. This avoids insufficient methanol activation and inadequate reaction activity caused by too low a photocatalyst addition (below 0.1 g / L), while preventing light shading, particle agglomeration, and excessive formaldehyde conversion side reactions caused by too high a addition (above 0.3 g / L), thus controlling raw material costs while ensuring catalytic efficiency.
[0036] The loading of platinum nanoparticles in the photocatalyst is 0.9wt%~1.1wt%, for example, 0.9wt%, 1.0wt%, 1.1wt%, etc. This platinum nanoparticle loading range of 0.9wt%~1.1wt% is compatible with the size control of platinum nanoparticles in this application, enabling uniform dispersion and loading of platinum nanoparticles on anatase phase titanium dioxide {001} nanocrystals. This avoids insufficient active sites and poor photogenerated carrier separation efficiency caused by excessively low platinum nanoparticle loading (below 0.9wt%), while also preventing agglomeration and exacerbated side reactions caused by excessively high platinum nanoparticle loading (above 1.1wt%). Simultaneously, it maximizes the utilization rate of precious metal platinum atoms, balancing catalytic performance and economic viability for industrial applications.
[0037] According to embodiments of this application, the ultraviolet light source includes any one of a light-emitting diode (LED), a mercury lamp, or a xenon lamp; the wavelength of the ultraviolet light source is 200nm~400nm, and the power is 50W~150W.
[0038] The band gap of anatase titanium dioxide {001} nanocrystals is about 3.2 eV, and their intrinsic light absorption is located in the ultraviolet region. The wavelength range of ultraviolet light sources from 200 to 400 nm can ensure that the photon energy emitted by the light source is sufficient to excite the anatase titanium dioxide {001} nanocrystals and generate the photogenerated electron-hole pairs necessary to drive the surface redox reaction.
[0039] A UV light source with a power range of 50W to 150W can provide sufficient photon flux within the reaction system to generate enough photogenerated carriers, thus ensuring the activity of the photocatalytic methanol dehydrogenation reaction. Using a lower power source (below 50W) will result in a lower photogenerated carrier generation rate, a decrease in the intrinsic reaction rate of methanol photocatalytic dehydrogenation, leading to a slow increase in formaldehyde and hydrogen concentrations and a significantly longer reaction cycle. Using a higher power source (above 150W) can, on the one hand, easily cause a significant temperature rise in the reaction system, generating a photothermal coupling effect that interferes with the intrinsic photocatalytic activity, making it impossible to maintain the constant room temperature required for the reaction; on the other hand, excessively high power may also induce non-target side reactions such as deep formaldehyde dehydrogenation and over-oxidation, and even change the main reaction pathway of methanol conversion, reducing formaldehyde selectivity. Simultaneously, excessively high power will accelerate the evaporation of the methanol aqueous solution, disrupting the concentration of the formaldehyde aqueous solution in the reaction system and the gas-liquid balance between the formaldehyde aqueous solution and the gaseous products (hydrogen), and exacerbating nonradiative recombination of photogenerated carriers, leading to a decrease in photon utilization efficiency.
[0040] In some specific embodiments, for example, a 100W LED lamp with an ultraviolet wavelength of 365nm can be used.
[0041] According to embodiments of this application, the preparation method of the photocatalyst includes: adding anatase phase titanium dioxide {001} nanocrystals, a platinum precursor, and an acidity regulator or alkalinity regulator to an alcohol solution to obtain a mixed solution with a pH value of 1~2 or 11~12; heating the mixed solution at 150℃~170℃ for 1h~2h, reducing the platinum precursor with the alcohol solution, and then calcining it at 350℃~400℃ for 0.5h~1h under an oxygen-containing inert atmosphere to obtain the photocatalyst.
[0042] According to some specific embodiments of this application, the heating reaction temperature can be, for example, 150°C, 155°C, 160°C, 165°C, 170°C, etc., and the time can be, for example, 1h, 1.5h, 2h, etc.; the calcination temperature can be, for example, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, etc., and the time can be, for example, 0.5h, 0.7h, 1h, etc.
[0043] According to some specific embodiments of this application, the oxygen-containing inert atmosphere can be a mixture of 10% oxygen (O2) and argon (Ar) (10% O2 / Ar).
[0044] According to the embodiments of this application, by using in-situ reduction of alcohols combined with mild calcination, platinum nanoparticles can be precisely controlled to be uniformly loaded on the surface of anatase phase titanium dioxide {001} nanocrystals without the use of organic stabilizers. Acidic or alkaline pH adjustment can effectively change the adsorption and reduction kinetics of platinum precursors and stabilize the average size of platinum nanoparticles in the range of 2nm to 6nm, further ensuring that Pt nanoparticles are uniformly dispersed, do not agglomerate, and do not coat.
[0045] Choosing a temperature range of 150℃ to 170℃ for alcoholic reduction ensures, on the one hand, that the platinum precursor is fully and rapidly reduced to form a uniformly dispersed platinum sol, guaranteeing a uniform loading of platinum nanoparticles on the anatase phase titanium dioxide {001} nanocrystals; on the other hand, it avoids the rapid aggregation and uncontrolled particle size of platinum atoms caused by excessively high temperatures (above 170℃), thus facilitating the controllable growth of Pt nanoparticle size through pH adjustment. Furthermore, the temperature range of 150℃ to 170℃ matches the boiling point of the alcohol solvent used, maintaining a stable liquid-phase reaction environment and preventing problems such as violent boiling, localized overheating, and uneven mass transfer, further ensuring a uniform loading of platinum nanoparticles.
[0046] The subsequent calcination process at 350–400℃ can thoroughly remove residual alcohol solvents, organic adsorbates, and potentially residual chlorine ligands from the synthesis process without excessively damaging the size of Pt nanoparticles and the structure of the Pt-TiO2 interface, while simultaneously improving the cleanliness and stability of the catalytic interface. The 350–400℃ temperature range also effectively prevents the anatase phase titanium dioxide {001} nanocrystals from undergoing a phase transition from anatase to rutile at higher temperatures (above 400℃), preserving the highly active {001} crystal facets. Furthermore, it optimizes the surface structure and interfacial electron transport capabilities of the photocatalyst, ultimately yielding a photocatalyst with high activity, selectivity, and stability.
[0047] According to the embodiments of this application, the mass ratio of anatase phase titanium dioxide {001} nanocrystals to platinum precursor is (90~110):1, for example, it can be 90:1, 100:1, 110:1, etc., to ensure that the platinum nanoparticle loading on the final photocatalyst is stable in the range of 0.9wt%~1.1wt%.
[0048] Platinum precursors include any one of chloroplatinic acid, chloroplatinate, and tetraamminenitrate platinum. The above-mentioned platinum precursors have good solubility in alcohol systems, their reduction potentials are compatible with alcoholic systems, the reduction process is mild and controllable, and there are no impurities left after calcination, which can ensure the cleanliness of the catalytic interface.
[0049] Alcohol solutions include any one of ethylene glycol, propylene glycol, and glycerol solutions. These alcohol solutions can act as both solvents and reducing agents, have a mild reducing ability, and can effectively disperse anatase phase titanium dioxide {001} nanocrystal carriers. They are suitable for reaction temperatures of 150℃~170℃ and are easily and completely removed afterward, leaving no residual impurities that affect the catalytic performance of the photocatalyst.
[0050] According to embodiments of this application, the acid regulator includes any one of hydrochloric acid, sulfuric acid, and nitric acid, with a concentration of 0.1M to 0.5M. Using the acid regulator can adjust the pH of the mixed solution to acidic conditions. When the pH of the mixed solution is 1 to 2, the average size of the platinum nanoparticles supported in the photocatalyst is 4 to 6 nm. This acidic condition (pH 1 to 2) can effectively inhibit the hydrolysis and dissociation process of the platinum precursor, reduce the reducing activity of the platinum precursor, and slow down the nucleation rate and reduce the number of nuclei formed in the platinum nanoparticles.
[0051] The alkalinity regulator includes any one of sodium hydroxide, potassium hydroxide, or ammonia solution, at a concentration of 0.1M to 0.5M. Using this alkalinity regulator, the pH of the mixed solution can be adjusted to alkalinity. When the pH of the mixed solution is 11 to 12, the average size of the platinum nanoparticles supported in the photocatalyst is 2 to 3.9 nm. Under these strongly alkaline conditions (pH 11 to 12), the platinum precursor in the system can achieve rapid reduction and instantaneous nucleation under alcothermal conditions.
[0052] Compared to an alkaline system with a pH of 11-12, an acidic system with a pH of 1-2 has a higher hydroxide (OH) content. - The concentrations differ by about 10 orders of magnitude, resulting in a fundamental difference in the nucleation rate of platinum precursors: the nucleation rate is faster under higher pH conditions (pH 11~12), and a large number of uniform crystal nuclei can be formed in a shorter time. Under the same platinum nanoparticle loading, more crystal nuclei mean that the amount of precursor available for each crystal nucleus is less, and ultimately platinum nanoparticles with smaller average size (2nm~3.9nm) can be obtained.
[0053] While theoretically increasing the pH value (pH value greater than 12) could synthesize platinum nanoparticles with smaller sizes (average size less than 2 nm), the platinum precursor exists in solution in anionic form. An excessively alkaline environment can cause strong electrostatic repulsion between anions, making it difficult for platinum nanoparticles to be effectively adsorbed and deposited on the surface of anatase phase titanium dioxide {001} nanocrystals. This can easily lead to a significant reduction in the actual loading of platinum nanoparticles. Therefore, this application controls the pH value adjusted by the alkaline regulator within the range of 11 to 12 to achieve a match between the size and loading of platinum nanoparticles.
[0054] According to the embodiments of this application, the prepared formaldehyde selectivity is higher than 91%, and the methanol conversion rate in the methanol solution is higher than 0.6%, breaking through the common technical bottleneck of "high activity accompanied by low selectivity, and high selectivity accompanied by low activity" in photocatalytic methanol conversion systems. Under anaerobic and mild light conditions, a synergistic balance between methanol conversion and selectivity is achieved. The formaldehyde selectivity of over 91% can suppress the side reactions of deep formaldehyde dehydrogenation and excessive oxidation, and CO... x The generation of byproducts such as CO and CO2 is low, avoiding the subsequent poisoning effect of CO on the photocatalyst. There is no need to set up additional post-processing units such as product purification and separation, simplifying the process flow and reducing equipment investment and operating costs. At the same time, it realizes the targeted high-value conversion of methanol into formaldehyde, a high-value basic chemical. The methanol conversion rate of more than 0.6% breaks through the limitations of traditional thermocatalytic methanol reforming, which requires high temperature and high energy consumption (200~300℃). Methanol conversion can be achieved using only ultraviolet light, reducing reaction energy consumption and carbon emissions. At the same time, it avoids the ineffective decomposition of methanol feedstock, improves feedstock utilization, and realizes the efficient synergistic co-production of formaldehyde and hydrogen. It takes into account the dual value of clean energy preparation and high-value chemical production, and has both catalytic stability and industrial-scale application prospects.
[0055] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with specific embodiments. Unless otherwise specified, specific techniques or conditions in the embodiments are conventional methods, which can be performed according to the techniques or conditions described in the literature in this field or according to the product instructions. It should be noted that, unless otherwise specified, the methods provided in this application are conventional methods, and the reactants and reagents can be obtained from publicly available commercial sources unless otherwise specified.
[0056] Example 1
[0057] This application provides a method for the photocatalytic conversion of methanol to formaldehyde and hydrogen. The specific method is as follows.
[0058] Weigh 0.7 g of anatase phase titanium dioxide {001} nanocrystals and disperse them in a three-necked flask containing 50 mL of ethylene glycol. Then add 1.42 mL of ethylene glycol solution of chloroplatinic acid hexahydrate (H2PtCl6·6H2O) (5 mg Pt / mL), followed by 2.5 mL of ethylene glycol solution of 0.25 M sodium hydroxide (NaOH). Adjust the pH of the system to 11.2 to obtain a homogeneous mixed solution.
[0059] The mixed solution was heated at 160℃ for 1 hour. After the reaction was completed, it was calcined at 400℃ for 0.5 hours under a 10% O2 / Ar atmosphere to obtain the photocatalyst, which was labeled as photocatalyst 1.
[0060] Under closed, anaerobic conditions, 40 mL of methanol-water solution (methanol to water volume ratio of 70:30) and 5 mg of photocatalyst were mixed and placed under a 100 W LED ultraviolet lamp with a wavelength of 365 nm to carry out the photocatalytic dehydrogenation of methanol to formaldehyde and hydrogen, thus preparing formaldehyde and hydrogen.
[0061] Example 2
[0062] This application provides a method for photocatalytic conversion of methanol to formaldehyde and hydrogen. The difference between this method and Example 1 is that 1.7 mL of a 0.25 M hydrogen chloride (HCl) solution in ethylene glycol is added to adjust the pH of the system to 1.8, resulting in a homogeneous mixed solution. The remaining steps are the same as in Example 1, and the resulting photocatalyst is labeled as photocatalyst 2.
[0063] Example 3
[0064] This application provides a method for photocatalytic conversion of methanol to formaldehyde and hydrogen. The difference between this method and Example 1 is that 5 mL of a 0.25 M hydrogen chloride (HCl) solution in ethylene glycol is added to adjust the pH of the system to 1.2, resulting in a homogeneous mixed solution. The remaining steps are the same as in Example 1, and the resulting photocatalyst is labeled as photocatalyst 3.
[0065] Example 4
[0066] This application provides a method for photocatalytic conversion of methanol to produce formaldehyde and hydrogen. The difference between this method and Example 1 is that the volume ratio of methanol to water is 90:10, while the remaining steps are the same as in Example 1.
[0067] Example 5
[0068] This application provides a method for photocatalytic conversion of methanol to produce formaldehyde and hydrogen. The difference between this method and Example 1 is that the volume ratio of methanol to water is 80:20, while the remaining steps are the same as in Example 1.
[0069] Example 6
[0070] This application provides a method for photocatalytic conversion of methanol to produce formaldehyde and hydrogen. The difference between this method and Example 1 is that the volume ratio of methanol to water is 60:40, while the remaining steps are the same as in Example 1.
[0071] Comparative Example 1
[0072] This application provides a comparative example of a method for photocatalytic conversion of methanol to formaldehyde and hydrogen. The difference between this method and Example 1 is that 80 mL of pure methanol (anhydrous system, methanol to water volume ratio of 100:0) and 10 mg of photocatalyst 1 are mixed, and the remaining steps are the same as in Example 1.
[0073] Comparative Example 2
[0074] This application provides a comparative example of a method for the photocatalytic conversion of methanol to produce formaldehyde and hydrogen. The difference between this method and Example 1 is that the volume ratio of methanol to water is 50:50; the remaining steps are the same as in Example 1.
[0075] Comparative Example 3
[0076] This application provides a comparative example of a method for photocatalytic conversion of methanol to formaldehyde and hydrogen. The difference between this method and Example 2 is that 80 mL of pure methanol (anhydrous system, methanol to water volume ratio of 100:0) and 10 mg of photocatalyst 2 are mixed, and the remaining steps are the same as in Example 2.
[0077] Comparative Example 4
[0078] This application provides a comparative example of a method for photocatalytic conversion of methanol to formaldehyde and hydrogen. The difference between this method and Example 3 is that 80 mL of pure methanol (anhydrous system, methanol to water volume ratio of 100:0) and 10 mg of photocatalyst 3 are mixed, and the remaining steps are the same as in Example 3.
[0079] The morphology of the photocatalysts prepared in Examples 1 to 3 was characterized using a field emission high-resolution transmission electron microscope (JEM-F200), and the size and dispersion of the platinum nanoparticles supported on the surface of the photocatalysts were tested.
[0080] Figure 1 These are high-resolution transmission electron microscope (TEM) images of the photocatalysts in Examples 1 to 3 of this application, wherein a is a TEM image of photocatalyst 1 in Example 1; b is a TEM image of photocatalyst 2 in Example 2; and c is a TEM image of photocatalyst 3 in Example 3.
[0081] like Figure 1 As shown, in the photocatalysts prepared in Examples 1 to 3, the platinum nanoparticles were uniformly dispersed on the surface of anatase phase titanium dioxide {001} nanocrystals without obvious agglomeration. Specifically, the average size of the platinum nanoparticles in photocatalyst 1 prepared in Example 1 was 2 nm; the average size of the platinum nanoparticles in photocatalyst 2 prepared in Example 2 was 4 nm; and the average size of the platinum nanoparticles in photocatalyst 3 prepared in Example 3 was 6 nm, achieving the control of platinum nanoparticle size under conditions without organic stabilizers.
[0082] Gas chromatography was used to detect the content and composition of gaseous products (H2, CO, CO2) before and after the photocatalytic reaction in Examples 1-6 and Comparative Examples 1-2. Ultraviolet-visible spectrophotometers were used to detect the formaldehyde content in the liquid products after the reaction using the acetylacetone spectrophotometric method. Nuclear magnetic resonance (NMR) was used to detect the formic acid content of the liquid byproduct. The methanol conversion rate and formaldehyde selectivity were calculated based on the gaseous products, formaldehyde, and formic acid production, using the following specific formulas.
[0083] Methanol conversion rate = formaldehyde production + formic acid production + CO x Amount produced / Total amount of methanol before reaction.
[0084] Formaldehyde selectivity = (Formaldehyde production / Formaldehyde production + Formic acid production + CO) x Generation amount.
[0085] Among them, CO x The amount generated is the sum of the amount of CO generated and the amount of CO2 generated.
[0086] Figure 2 This is a comparison graph showing the hydrogen generation rate, formaldehyde generation rate, and hydrogen to formaldehyde yield ratio in the photocatalytic reactions of Comparative Examples 1, 3, and 4 of this application.
[0087] Table 1 shows the specific data on hydrogen generation rate, formaldehyde generation rate, and hydrogen to formaldehyde production ratio (hydrogen / formaldehyde) in the photocatalytic reactions of Comparative Examples 1, 3, and 4 of this application.
[0088] Table 1
[0089]
[0090] like Figure 2 As shown in Table 1, the photocatalytic performance of photocatalysts loaded with platinum nanoparticles of different sizes under pure methanol conditions exhibits a significant size dependence: as the size of the platinum nanoparticles loaded on the photocatalyst decreases from 6 nm to 2 nm, the hydrogen and formaldehyde generation rates both show a significant upward trend. Among them, photocatalyst 1 used in Comparative Example 1 (with an average platinum nanoparticle size of 2 nm) exhibits the best photocatalytic activity, with a hydrogen generation rate of approximately 126.28 mmol·g⁻¹. -1 ·h -1The hydrogen production efficiency was 1.85 times that of photocatalyst 2 (with an average size of 4 nm platinum nanoparticles) used in Comparative Example 3 and 4.86 times that of photocatalyst 3 (with an average size of 6 nm platinum nanoparticles) used in Comparative Example 4, respectively. This phenomenon can be attributed to the fact that smaller platinum nanoparticles have more surface reactive sites, a larger specific surface area, and better photogenerated electron-hole separation efficiency, which can drive the methanol dehydrogenation reaction more efficiently. Meanwhile, the hydrogen to formaldehyde production ratio (H2 / HCHO) remained stable in the range of approximately 1.07 to 1.08 in the photocatalytic reactions of Comparative Examples 1 and 3, but decreased to approximately 1.00 in the photocatalytic reaction of Comparative Example 4, further verifying that smaller platinum nanoparticles have a stronger enhancing effect on the directional dehydrogenation pathway of methanol. Based on this, this application subsequently selected photocatalyst 1, which has the best hydrogen evolution activity, to carry out subsequent photocatalytic reactions in methanol-water solutions with different volume ratios.
[0091] Figure 3 This is a comparison chart of the hydrogen generation rate, formaldehyde generation rate, and hydrogen to formaldehyde yield ratio in the photocatalytic reactions of Examples 1 to 3 of this application.
[0092] like Figure 3 As shown, as the size of the platinum nanoparticles supported on the photocatalyst decreased from 6 nm to 2 nm, both the hydrogen generation rate and the formaldehyde generation rate significantly increased. Among them, Example 1 (the size of the platinum nanoparticles supported on photocatalyst 1 was 2 nm) exhibited the best catalytic activity, with a hydrogen generation rate of 602.91 mmol·g⁻¹. -1 ·h -1 The formaldehyde formation rate reached 416.80 mmol·g -1 ·h -1 Meanwhile, the hydrogen to formaldehyde production ratio (hydrogen / formaldehyde) increased linearly with decreasing platinum nanoparticle size, gradually increasing from approximately 1.06 in the system of Example 3 (where the platinum nanoparticles supported on photocatalyst 3 had a size of 6 nm) to approximately 1.44 in the system of Example 1. This indicates that small-sized platinum nanoparticles can enhance the main reaction pathway of methanol-directed dehydrogenation, improving the efficiency of formaldehyde and hydrogen co-production while effectively suppressing side reactions such as deep formaldehyde dehydrogenation, thus achieving synergistic optimization of photocatalytic activity and formaldehyde selectivity.
[0093] And further comparison Figure 2 and Figure 3 It can be seen that in the pure methanol system, the ratio of hydrogen to formaldehyde production is basically no more than 1.1, which is basically in line with the stoichiometric relationship of one molecule of formaldehyde and one molecule of hydrogen produced by the decomposition of methanol. However, in the photocatalytic reactions of Examples 1 to 3, this ratio is greater than 1.05, and can reach 1.4 in the photocatalytic reaction of Example 1. This proves that the participation of water introduces additional proton transfer and hydrogen production channels into the reaction system, promoting the generation of additional hydrogen.
[0094] Figure 4 This is a comparison graph showing the hydrogen generation rate, formaldehyde generation rate, and hydrogen to formaldehyde yield ratio in the photocatalytic reactions of Examples 1, 4-6, and Comparative Examples 1-2 of this application.
[0095] Table 2 presents comparative data on methanol conversion rate, formaldehyde selectivity, and hydrogen and formaldehyde generation rates in the photocatalytic reactions of Examples 1 to 6 and Comparative Examples 1 to 2 of this application.
[0096] Table 2
[0097]
[0098] like Figure 4 As shown in Table 2, within the methanol volume concentration range of 60%–90% (i.e., the methanol-to-water volume ratio of (90–60):(10–40)), all examples achieved formaldehyde selectivity exceeding 91% and methanol conversion exceeding 0.6%. Specifically, when the methanol volume concentration was 70% and the average size of the platinum nanoparticles supported on the photocatalyst was 2 nm, the system exhibited superior catalytic activity and a good balance between hydrogen and formaldehyde generation rates. When the methanol volume concentration was below 60% (e.g., in Comparative Example 2, the methanol-to-water volume ratio was 50:50), although the methanol conversion rate slightly increased to 1.42%, the catalytic activity decreased significantly, and the hydrogen generation rate dropped sharply to 377.65 mmol·g⁻¹. -1 ·h -1 The formaldehyde selectivity also decreased to 90.83%. This was because excess water further crowded out the adsorption sites of methanol on the photocatalyst surface, resulting in insufficient methanol coverage. Photogenerated holes could not be effectively cleared, and recombination of photogenerated carriers intensified. Simultaneously, the hydroxyl radicals generated by excess water easily triggered excessive oxidation of formaldehyde, leading to a simultaneous decline in selectivity and activity. When the methanol volume concentration was 100% (as in Comparative Example 1, a pure methanol anhydrous system), both catalytic activity and methanol conversion were at low levels, with a hydrogen generation rate of only 126.28 mmol·g⁻¹. -1 ·h -1 The methanol conversion rate was only 0.24%. Although the deep dehydrogenation side reaction of formaldehyde was suppressed to the greatest extent in the anhydrous system and the formaldehyde selectivity reached 97.03%, it completely lost its industrial application value. This result proves that the coupling synergistic effect of water and photocatalyst cannot be utilized in the pure methanol anhydrous system. It cannot promote the formation of methoxy intermediates through water dissociation, nor can it remove the CO poisoning sites generated during the reaction. As a result, the active sites are continuously poisoned, the reaction kinetics are severely hindered, and the formaldehyde desorption cannot be accelerated by water. Instead, formaldehyde accumulates on the surface and causes side reactions, ultimately leading to poor catalytic performance.
[0099] Meanwhile, through comparison of Examples 1 to 3, the rationality of the controllability range of the average size of platinum nanoparticles loaded on the photocatalyst from 2 nm to 6 nm was verified.
[0100] If the average size of platinum nanoparticles is less than 2 nm, their stability will decrease and their surface energy will be higher. During the alcoholic reduction and calcination stages of photocatalyst preparation, as well as during the photocatalytic reaction, irreversible agglomeration and sintering growth are likely to occur, making it impossible to stably maintain a high proportion of interfacial active sites, resulting in rapid decay of catalytic performance. Furthermore, the high proportion of low-coordination atoms on the surface of platinum nanoparticles with an average size of less than 2 nm will have an excessively strong activation ability for the CH bonds of formaldehyde molecules, easily triggering deep dehydrogenation and excessive oxidation side reactions of formaldehyde, generating large amounts of CO and formate. This not only leads to a decrease in formaldehyde selectivity but also causes the active sites to be poisoned by CO, losing the synergistic coupling advantage with water. In addition, although increasing the pH value in principle can prepare photocatalysts with smaller sizes (average size less than 2 nm) of platinum nanoparticles, the platinum precursor exists in the form of anions in the solution. An excessively alkaline environment will cause strong electrostatic repulsion between anions, making it difficult for platinum nanoparticles to be effectively adsorbed and deposited on the surface of anatase phase titanium dioxide {001} nanocrystals. This can easily lead to a significant reduction in the actual loading amount, making it difficult for platinum nanoparticles to be effectively loaded.
[0101] When the average size of platinum nanoparticles exceeds 6 nm, the proportion of active sites at the Pt-TiO2 interface decreases. As the size increases, the perimeter-to-volume ratio of the platinum nanoparticle interface decreases non-linearly, reducing platinum atom utilization. Simultaneously, it fails to effectively activate the catalytic activity of adjacent titanium dioxide support sites, making it difficult to achieve a synergistic catalytic effect between the Pt-TiO2 interface active sites and the titanium dioxide support sites. Consequently, the catalytic activity of the photocatalyst continues to decline (e.g., in Example 3, the hydrogen generation rate of 6 nm platinum nanoparticles has decreased to 248.24 mmol·g⁻¹). -1 ·h -1 ).
[0102] In summary, this application maximizes the synergistic effect of the photocatalyst and water by limiting the size of the platinum nanoparticles loaded on the photocatalyst to an optimized range of 2nm to 6nm, and combining it with a reaction system of methanol to water volume ratio of (90~60):(10~40). This achieves synergistic optimization of catalytic activity, product selectivity, feed conversion rate and operational stability, and solves the core bottleneck of existing technologies that cannot simultaneously achieve both activity and selectivity.
[0103] The above specific embodiments further illustrate the purpose, technical solution and beneficial effects of this application. It should be understood that the above are only specific embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for photocatalytic conversion of methanol to formaldehyde and hydrogen, characterized in that, The method includes: Under closed, oxygen-free conditions, a methanol aqueous solution and a photocatalyst were mixed and placed under an ultraviolet light source to carry out a photocatalytic dehydrogenation reaction of methanol to produce formaldehyde and hydrogen, thus preparing formaldehyde and hydrogen. The photocatalyst is anatase titanium dioxide {001} nanocrystals with platinum nanoparticles loaded on the surface, and the average size of the platinum nanoparticles is 2nm~6nm. The amount of photocatalyst added to the methanol-water solution is 0.1 g / L to 0.3 g / L; The loading of platinum nanoparticles in the photocatalyst is 0.9wt%~1.1wt%; The photocatalyst is obtained by the following method: Add anatase-phase titanium dioxide {001} nanocrystals, platinum precursor, and acidity or alkalinity regulator to an alcohol solution to obtain a mixed solution with a pH of 1-2 or 11-12. The mixed solution was heated at 150℃~170℃ for 1h~2h, the platinum precursor was reduced with an alcohol solution, and then calcined at 350℃~400℃ for 0.5h~1h under an oxygen-containing inert atmosphere to obtain the photocatalyst. The volume ratio of methanol to water in the methanol-water solution is (90~60):(10~40).
2. The method according to claim 1, characterized in that, The volume ratio of methanol to water is 70:
30.
3. The method according to claim 1, characterized in that, The average size of the platinum nanoparticles is 2 nm.
4. The method according to claim 1, characterized in that, The ultraviolet light source is any one of light-emitting diode, mercury lamp, and xenon lamp; The ultraviolet light source has a wavelength of 200nm~400nm and a power of 50W~150W.
5. The method according to claim 1, characterized in that, The mass ratio of the anatase phase titanium dioxide {001} nanocrystals to the platinum precursor is (90~110):1; The platinum precursor is any one of chloroplatinic acid, chloroplatinate, and tetraamminenitrate platinum. The alcohol solution is any one of ethylene glycol solution, propylene glycol solution, and glycerol solution.
6. The method according to claim 1, characterized in that, The acidity regulator is any one of hydrochloric acid, sulfuric acid, and nitric acid, with a concentration of 0.1M to 0.5M; The alkalinity regulator is any one of sodium hydroxide, potassium hydroxide, or ammonia water, with a concentration of 0.1M to 0.5M.
7. The method according to claim 1, characterized in that, When the pH of the mixed solution is 11-12, the average size of the platinum nanoparticles is 2nm-3.9nm; When the pH of the mixed solution is 1 to 2, the average size of the platinum nanoparticles is 4 nm to 6 nm.
8. The method according to claim 1, characterized in that, The selected formaldehyde obtained has a selectivity of over 91%, and the conversion rate of methanol in the methanol aqueous solution is over 0.6%.
Citation Information
Patent Citations
Method of preparing ethylene glycol by photo-catalytic formaldehyde conversion
CN103864576A
Catalyst for anoxic dehydrogenation of methanol, and application thereof
CN105170145A